Equilibrium climate sensitivity increases with aerosol concentration due to changes in precipitation efficiency - G. Dagan (Atmospheric Chemistry and Physics, 2022)
How Earth's climate reacts to anthropogenic forcing is one of the most burning questions faced by today's scientific community. A leading source of uncertainty in estimating this sensitivity is related to the response of clouds. Under the canonical climate-change perspective of forcings and feedbacks, the effect of anthropogenic aerosols on clouds is categorized under the forcing component, while the modifications of the radiative properties of clouds due to climate change are considered in the feedback component. Each of these components contributes the largest portion of uncertainty to its relevant category and is largely studied separately from the other. In this paper, using idealized cloud-resolving radiative–convective-equilibrium simulations, with a slab ocean model, we show that aerosol–cloud interactions could affect cloud feedback. Specifically, we show that equilibrium climate sensitivity increases under high aerosol concentration due to an increase in the short-wave cloud feedback. The short-wave cloud feedback is enhanced under high-aerosol conditions due to a stronger increase in the precipitation efficiency with warming, which can be explained by higher sensitivity of the droplet size and the cloud water content to the CO2 concentration rise. These results indicate a possible connection between cloud feedback and aerosol–cloud interactions.